Some differences between the visual and auditory memories in the short-term memory - Hamada, Jiro (Shinrigaku kenkyū, 1990)
In order to clarify the differences between the visual and the auditory memories and the interference effect between them, a paired presentation method was developed. In this method, the subject under the experimental condition memorized two independent sequences of random digits, which were presented simultaneously digit by digit, the digits of the one sequence being presented visually and the digits of the other auditorily. After the presentation, subjects were asked to recall first either the visual or the auditory digit sequence, and then the other sequence. The subject under the control condition, on the other hand, memorized one sequence of random digits which were presented either visually or auditorily, and after recalling them memorized another sequence of random digits presented in the other modality. The results can be summarized as follows. (1) Under the experimental as well as under the control conditions, the recency effect appeared in the auditory memory task, but it did not in the visual memory task. (2) The performance for visual by presented digits under the experimental condition was lower than that under the control condition, whereas the performance for auditorily presented digits under the former was equal to that under the latter. The results presented might suggest that: (1) there are independent visual and auditory memories in the short-term memory; and (2) the memorizing of the auditory materials interferes with the memorizing of the visual one, but the latter does not interfere with the former.